1994
DOI: 10.1038/371297a0
|View full text |Cite|
|
Sign up to set email alerts
|

The ancient regulatory-protein family of WD-repeat proteins

Abstract: WD proteins are made up of highly conserved repeating units usually ending with Trp-Asp (WD). They are found in all eukaryotes but not in prokaryotes. They regulate cellular functions, such as cell division, cell-fate determination, gene transcription, transmembrane signalling, mRNA modification and vesicle fusion. Here we define the common features of the repeating units, and criteria for grouping such proteins into functional subfamilies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
1,181
2
13

Year Published

1996
1996
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,397 publications
(1,216 citation statements)
references
References 64 publications
20
1,181
2
13
Order By: Relevance
“…Cdc34 is found to act in concert with a novel E3 (SCF) comprising a multiprotein complex composed of Cdc4, Cdc53 and Skp1 (Bai et al 1996;Mathias et al 1996;Willems et al 1996). Cdc4 contains two motifs, the F-box and WD-repeats (Neer et al 1994;Bai et al 1996). The F-box, consisting of around 40 amino acid residues, is found in a number of proteins from yeast to human, which has been proposed to be responsible for binding to another evolutionarily conserved protein Skp1.…”
Section: Introductionmentioning
confidence: 99%
“…Cdc34 is found to act in concert with a novel E3 (SCF) comprising a multiprotein complex composed of Cdc4, Cdc53 and Skp1 (Bai et al 1996;Mathias et al 1996;Willems et al 1996). Cdc4 contains two motifs, the F-box and WD-repeats (Neer et al 1994;Bai et al 1996). The F-box, consisting of around 40 amino acid residues, is found in a number of proteins from yeast to human, which has been proposed to be responsible for binding to another evolutionarily conserved protein Skp1.…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of the primary sequence of PREB revealed that it is a novel protein distinct from that of PIT1. PREB protein contained three motifs (WD I, WD II and WD III) possessing a significant degree of homology to the WD repeat consensus, thus suggesting that PREB was a member of the WD-repeat protein family [21]. The highly conserved WD-repeats within PREB exhibit sequence similarity to a subset of this family, consisting of proteins shown to act as gene regulators [21].…”
Section: Discussionmentioning
confidence: 99%
“…Several lines of observation suggest that Bop1 may function as a regulatory protein. First, all other WD40 proteins studied to date have been implicated in regulatory activities (Neer et al, 1994;Neer and Smith, 1996). Second, the presence of PEST sequences suggests that Bop1 may be short-lived, also pointing to possible regulatory functions (Rechsteiner and Rogers, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…The most prominent feature of these domains is that they are rich in acidic and serine residues and contain PEST sequences, which are often found in short-lived regulatory proteins (Rechsteiner and Rogers, 1996). The amino acid sequence of Bop1 contains several motifs, known as WD40 (or b-transducin) repeats (Figure 8), which are found in a large number of regulatory proteins (Neer et al, 1994;Neer and Smith, 1996) and may be involved in protein-protein interactions (Wall et al, 1995;Lambright et al, 1996;Sondek et al, 1996). The WD40 motif encompasses approximately 40 amino acid residues with several conserved features, including a characteristic Trp-Asp (WD) dipeptide.…”
Section: Clone B5-35 Identi®es a Novel Wd40 Repeat Protein Bop1mentioning
confidence: 99%
See 1 more Smart Citation